Retrospective study of diseases of cattle at Adamdighi Veterinary Hospital, Bogra (Bangladesh Veterinarian, 2016)
A retrospective epidemiological study was undertaken at the Adamdighi Veterinary Hospital, Bogra from January 2012 to December 2014 to determine the occurrence of cattle diseases. According to the diseases register, a total of 12403 sick animals were examined and 7208 cases of cattle diseases were identified. About 44.7% were parasitic, 37.8% general systemic affections, 14.2% infectious, 1.3% reproductive, 1.2% poisoning and 0.8% metabolic diseases. The common diseases were worm infestation (34.2%), pneumonia (8.7%), foot and mouth disease (2.5%), mastitis (1.9%), black quarter (0.6%), haemorrhagic septicaemia (0.5%), simple indigestion (11.9%), diarrhoea (11.7%), fever (7.5%), navel ill (2.6%), bloat (2.0%), calf scour (1.7%), organo-phosphorus poisoning (1.2%), retained placenta (0.8%) and abortion (0.6%). About 2397 cases (33.3%) were in male and 4811 cases (67.7%) in female. Animals aged between 1-3 (A2) years had highest occurrences (34.3%) of diseases but lowest 17.1% occurrences were in cattle between 8-15 years (A4) of age. Disease occurrence was higher (37.3%) in summer (March June) followed by (32.5%) rainy (July October) and lowest (30.3%) in winter season (November February). Gastrointestinal diseases (n = 3665) were most common but lower cases of hematopoietic system were identified (n = 107). This study showed the pattern of diseases that might help to identify the risk factors of these maladies in this area.Bangl. vet. 2015. Vol. 32, No. 1, 7-12